Personality characteristics associated with the dream lucidity ability: fact or fiction - Gackenbach, Jayne (My University, 1985)
Two areas of particular interest to me about lucid dreaming are: (1) individual differences; is there a certain type of person who is likely to have these experiences and (2) systematic analysis of the content of the experience. I’ll be talking about the content analysis later. Right now, I’m going to talk about the type of person who is likely to have this dream. A complete review of our program of research on in-dividual differences will soon be available (Snyder & Gackenbach, in press).
Keywords: dreams; males; females